2019
DOI: 10.1111/bph.14571
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Short lipopeptides specifically inhibit the growth of Propionibacterium acnes with dual antibacterial and anti‐inflammatory action

Abstract: Background and Purpose: Propionibacterium acnes (P. acnes) is a Gram-positive bacterium associated with the skin disorder acne. In this study, we determined the importance of fatty acids in the life habitat of P. acnes; we tested our lipopeptide library in an attempt to create potent P. acnes-specific antimicrobial agents. Experimental Approach: Antimicrobial activity was determined by the minimal inhibitory concentration (MIC). Lipids from P. acnes were used to explore the mode of action. RAW264.7 cells respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Acne may be relieved by the administration of several exogenous drugs. Some small peptides, such as melittin and short lipopeptides, can protect cells from inflammatory responses induced by C. acnes and may even have direct antibacterial effects [ 48 ]. Several biologically active compounds extracted from plants have been found to inhibit the occurrence of acne to varying degrees [ 49 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acne may be relieved by the administration of several exogenous drugs. Some small peptides, such as melittin and short lipopeptides, can protect cells from inflammatory responses induced by C. acnes and may even have direct antibacterial effects [ 48 ]. Several biologically active compounds extracted from plants have been found to inhibit the occurrence of acne to varying degrees [ 49 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…To improve the structural stability and activity of the peptide, its structure is modified via various methods including acetylation, amidation, amino acid replacement, D-amino acid substitution, the deletion of inactive amino acids, cyclization into a cyclic peptide, and fatty acid modification into a lipopeptide. Recent studies have shown that cyclic peptides and lipopeptides can enhance the biological activity and stability of peptides [ 32 , 33 , 34 , 35 ]. Fatty acids, a class of essential nutrients, regulate a wide range of vital processes and disorders including diabetes, cancer, and cardiovascular disease [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%